Analysis of Entropy Generation in Natural Convection of Nanofluid inside a Square Cavity Having Hot Solid Block: Tiwari and Das' Model - Sheremet, Mikhail A.; Öztop, Hakan Fehmi; Pop, Ioan; Abu-Hamdeh, Nidal (Mdpi Ag, 2016)
A computational work has been performed in this study to investigate the effects of solid isothermal partition insertion in a nanofluid filled cavity that is cooled via corner isothermal cooler. Mathematical model formulated in dimensionless primitive variables has been solved by finite volume method. The study is performed for different geometrical ratio of solid inserted block and corner isothermal cooler, Rayleigh number and solid volume fraction parameter of nanoparticles. It is observed that an insertion of nanoparticles leads to enhancement of heat transfer and attenuation of convective flow inside the cavity.
Keywords: natural convection; entropy generation; nanofluid; corner cooling; hot centered obstacle